A política de garantia de preços mínimos (PGPM) e estoques públicos brasileiros no contexto da pandemia da COVID-19: o caso do abastecimento de arroz e seus impactos para a segurança alimentar - Oliveira, Jessica Gomes Siqueira de (Universidade Federal de São Carlos, 2022)
Access to food is one of the principles of food security, which is presented as one of the premises for promoting the dignity of the human person. The guarantee of food security and the human right to adequate food (DHAA) guide the policies developed by the public administration, whose aim is to promote social security. In this context, ensuring continuous food supply, guaranteeing access to food, is the main objective of the State's action mechanisms. The Minimum Price Guarantee Policy (PGPM) is one of the policies aimed at this purpose, as it works to correct market failures, promoting income for farmers and affordable food prices for consumers. However, although the State's action is regulated in this regard, there was a considerable increase in the price of basic food items during the COVID-19 pandemic established in Brazil and around the world. Among them, rice (Oryza sativa L.) stands out, whose price rise directly affected the basic diet of the poorest Brazilian population. Therefore, the objective of the present study is to investigate state action and its adequacy in guaranteeing supply and regulating product prices. To this end, information on public and private rice stocks, present in the National Supply Company (CONAB) database, was analyzed. As a result, it was possible to conclude that state management in promoting food security during the COVID-19 health crisis was unsatisfactory. Knowing the scenario of currency devaluation and the consequent increase in exports, in addition to the increase in domestic demand, it was predictable that there would be a market imbalance between supply and demand and an increase in prices. However, the amount of rice stored in public stocks proved to be deficient in relation to national production, not meeting the conditions for intervention to guarantee food security for the population.
The minimum price guarantee policy (PGPM) and brazilian public stocks in the context of the COVID-19 pandemic: the case of rice supply and its impacts on food safety
Keywords: Segurança alimentar; Políticas econômicas; Inflação; Arroz; COVID-19; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS